Upaya Peningkatan Kreativitas dan Kemampuan Inovasi Dosen - Hidayati , Syafaatul; Sholeh, Badrus (Aufklarung: Jurnal Pendidikan, Sosial dan Humaniora, 2022)
The purpose of this study is to find out how efforts to increase creativity and innovation ability for lecturers. The research conducted is with literature studies. The results obtained are that lecturers are a very important component in efforts to improve the quality of graduates. For this reason, lecturers should start improving themselves starting with improving the quality that can support their performance. Lecturer creativity and innovation are needed in an effort to support the achievement of the learning goals set. For this reason, lecturers really need adjustments in using models and learning media that are actively creative and innovative during the learning process both offline and offline.